Evaluation of the Healthy Living Community Movement (GERMAS) Effectiveness in Bima City - Kurniawati, Serosa Andi; Saimi, Saimi; Sastrawan, Sastrawan (IKIP Mataram, 2024)
The Healthy Living Community Movement (GERMAS) is a coordinated national initiative to promote healthy behavior and improve quality of life through family and community engagement. This study explores the implementation of GERMAS in Bima City, focusing on the effectiveness of health promotion strategies like advocacy, socialization, and public campaigns across Community Health Centers (Puskesmas) and related Regional Apparatus Organizations (OPD). A qualitative descriptive research design grounded in postpositivist philosophy was employed, with data collected through triangulated interviews and observations. Findings indicate that GERMAS health promotion activities are well-established but limited to specific actions, lacking comprehensive integration across sectors. Efforts remain primarily confined to isolated activities, such as promoting a Clean and Healthy Lifestyle (PHBS) and disease prevention, rather than fostering collaborative, multi-sectoral engagement. Future implementation should strengthen cross-sector partnerships and expand routine practices, including regular physical activity, increased fruit and vegetable intake, and health check-ups every six months. The study offers foundational insights for developing enhanced strategies and policies for GERMAS integration in community health frameworks.